Correlation between piezoelectric and magnetic properties of Fe and Sm co-substituted potassium niobate piezoelectric ceramics - Swami M.; Verma O.N.; Tomar V.; Kumar M.; Srivastav K.K.; Sathe V.; Jha P.A.; Singh P. (My University, 2025)
A piezoelectric material KNbO3 has been co-substituted with the magnetic ions Sm3+ and Fe3+ in order to explore the relation between piezoelectricity and magnetism. The samples K1-xSmxNb1-xFexO3 [x = 0.0-0.1] were synthesized using a solid state reaction route, after estimating the structural stability with the substitution. Structural studies were employed using XRD with Rietveld refinement and Raman analysis suggesting Amm2 symmetry. Also, the transition temperature was observed to change with the increase in Sm and Fe content. This transition temperature was also confirmed through high temperature XRD and high temperature Raman results. The dielectric and piezoelectric properties were found to be in correlation with the intensity of Raman modes for substituted samples, indicating better ferroelectricity at x = 0.05. A correlation between piezoelectric and magnetic properties was established in terms of the coercive field and exchange energy. © the Owner Societies.